2020
DOI: 10.1109/access.2019.2962221
|View full text |Cite
|
Sign up to set email alerts
|

Can the Exchange Rate Be Used to Predict the Shanghai Composite Index?

Abstract: Stock index price forecasting is a consistent focus of business intelligence. Various factors influence stock index price forecasting, such as technical indicators, financial news, business status, and the macroeconomics situation. In addition, many studies have shown that the exchange rate is related to the stock index price; however, no study has examined whether the exchange rate can be used to forecast stock index prices. Therefore, this paper focuses on this topic and uses exchange rate to predict China s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Sensoy and Tabak [6] analyzed the dependence between the stock market and exchange rate prices, and the experimental results showed that exchange rate prices were correlated with stocks. Zhang et al [7] used the SVM model to prove that the exchange rate price could be applied to the index prediction. In this study, the exchange rate price of RMB and USD for 7 years from January 1, 2013 to December 31, 2019 is chosen as the exchange rate characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…Sensoy and Tabak [6] analyzed the dependence between the stock market and exchange rate prices, and the experimental results showed that exchange rate prices were correlated with stocks. Zhang et al [7] used the SVM model to prove that the exchange rate price could be applied to the index prediction. In this study, the exchange rate price of RMB and USD for 7 years from January 1, 2013 to December 31, 2019 is chosen as the exchange rate characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that reducing the number of TIs has a positive impact on the ability of prediction. Zhang et al [30] used the TIs as input values generated from the exchange rate and employed support vector machine (SVM) to predict the stock index price of China. The results confirmed that the technical indicators of the exchange rate can be used to improve the prediction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different kinds of machine learning (ML) models have been used for short term financial market prediction [5]- [12] and have obtained satisfying results. This shows a promising direction to apply predictive future return as expected return in building portfolio models.…”
Section: Introductionmentioning
confidence: 99%